The Influence of Leadership Style on Employee Conflict Intensity and Resolution: A Multidisciplinary Perspective - Syarweny , Narulita; Sukardi, Sukardi (CV. HEI PUBLISHING INDONESIA, 2025)
The purpose of this study is to examine, from a multidisciplinary standpoint, how leadership style affects the severity and settlement of employee conflicts. A questionnaire evaluating leadership style, conflict severity, and conflict resolution techniques was used to gather data from 100 respondents using a quantitative method and a cross-sectional design. Regression analysis results indicated that authoritarian leadership style positively contributed to rising conflict intensity (β = 0.32, p <.01), but transformational leadership style significantly decreased conflict intensity (β = -0.45, p <.001). Furthermore, it was demonstrated that cooperative conflict resolution techniques were successful in lowering stress at work (r = -.56, p <.001). These results demonstrate how crucial flexible and communicative leaders are to fostering a positive and effective workplace. Nevertheless, this study has drawbacks, such as a sample size restricted to a few business sectors and a cross-sectional design that precludes drawing conclusions about causality. It is advised that further study be done to examine how technology use and organizational cultural setting affect dispute resolution.